2016
DOI: 10.1371/journal.pone.0153768
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of ApoL1 in Zebrafish Larvae Affects the Glomerular Filtration Barrier and the Expression of Nephrin

Abstract: APOL1, a secreted high-density lipoprotein, is expressed in different human tissues. Genetic variants of APOL1 are described to be associated with the development of end stage renal diseases in African Americans. In human kidney, APOL1 is mainly expressed in podocytes that are responsible for proper blood filtration. Since mice do not express ApoL1, the zebrafish is an ideal model to study the role of ApoL1. Injection of morpholinos against zApoL1 into zebrafish eggs and larvae, respectively, induces severe ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…In normal human kidney the APOL1 protein localizes to the podocyte, the proximal tubule and the endothelium of extraglomerular arterioles and small arteries 27 , a finding subsequently replicated by others 28, 29 . Interestingly, the amount of APOL1 protein in the podocyte and proximal tubules was decreased in FSGS or HIV associated nephropathy (HIVAN), two kidney diseases associated with APOL1 risk variants 27, 29 .…”
Section: Apol1 Tissue and Cellular Distributionmentioning
confidence: 59%
See 2 more Smart Citations
“…In normal human kidney the APOL1 protein localizes to the podocyte, the proximal tubule and the endothelium of extraglomerular arterioles and small arteries 27 , a finding subsequently replicated by others 28, 29 . Interestingly, the amount of APOL1 protein in the podocyte and proximal tubules was decreased in FSGS or HIV associated nephropathy (HIVAN), two kidney diseases associated with APOL1 risk variants 27, 29 .…”
Section: Apol1 Tissue and Cellular Distributionmentioning
confidence: 59%
“…Although inflammatory mediators consistently increase APOL1 expression in vitro , immunohistochemical studies of human kidney sections of individuals with kidney diseases demonstrate decreased abundance of APOL1 protein in the podocyte and proximal tubule 27, 29 . Subjects with kidney diseases and the APOL1 risk genotype [two risk alleles] have similar APOL1 abundance by immunohistology compared to subjects with kidney disease and the low risk genotype [one on no risk alleles].…”
Section: Apol 1 Abundance and Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously shown that the overall fluorescence intensity of APOL1 signal in the glomeruli of focal segmental glomerulosclerosis (FSGS) and HIV-associated nephropathy (HIVAN) samples was diminished relative to glomeruli from samples without renal pathology (12,14). In this study, we further characterized APOL1 localization and distribution in podocytes to determine if these phenotypes were dependent upon kidney disease diagnosis or APOL1 genotype.…”
Section: Apol1 Localization Does Not Vary With Disease Diagnosis or Rmentioning
confidence: 88%
“…APOL1-coding polymorphisms, G1 and G2, encode APOL1 proteins that circumvent SRA-dependent resistance and restore parasite killing, but, if present on both alleles, they markedly increase CKD odds in African American patients (2,3). We and others have shown that APOL1 is localized in human kidney glomeruli (12)(13)(14) and that circulating APOL1 levels do not associate with categorical or quantitative CKD phenotypes (15,16). Others have shown that poor kidney allograft outcomes are associated with the APOL1 genotype of the transplanted kidney but not the recipient (17,18).…”
Section: Introductionmentioning
confidence: 88%